Effects of online and offline trigeminal nerve stimulation on visuomotor learning - Arias, Diego E.; Buneo, Christopher A. (Frontiers in Human Neuroscience, 2024)
A current thrust in neurology involves using exogenous neuromodulation of cranial nerves (e.g, vagus, trigeminal) to treat the signs and symptoms of various neurological disorders. These techniques also have the potential to augment cognitive and/or sensorimotor functions in healthy individuals. Although much is known about the clinical effects of trigeminal nerve stimulation (TNS), effects on sensorimotor and cognitive functions such as learning have received less attention, despite their potential impact on neurorehabilitation. Here we describe the results of experiments aimed at assessing the effects of TNS on motor learning, which was behaviorally characterized using an upper extremity visuomotor adaptation paradigm.In Experiment 1, effects of offline TNS using clinically tested frequencies (120 and 60 Hz) were characterized. Sixty-three healthy young adults received TNS before performing a task that involved reaching with perturbed hand visual feedback. In Experiment 2, the effects of 120 and 60 Hz online TNS were characterized with the same task. Sixty-three new participants received either TNS or sham stimulation concurrently with perturbed visual feedback. Experiment 1 results showed that 60 Hz stimulation was associated with slower rates of learning than both sham and 120 Hz stimulation, indicating frequency-dependent effects of TNS. Experiment 2, however, showed no significant differences among stimulation groups. A post-hoc, cross-study comparison of the 60 Hz offline and online TNS results showed a statistically significant improvement in learning rates with online stimulation relative to offline, pointing to timing-dependent effects of TNS on visuomotor learning.The results indicate that both the frequency and timing of TNS can influence rates of motor learning in healthy adults. This suggests that optimization of one or both parameters could potentially increase learning rates, which would provide new avenues for enhancing performance in healthy individuals and augmenting rehabilitation in patients with sensorimotor dysfunction resulting from stroke or other neurological disorders.